A nyilvános gyakorlatbavétel mint újdonságrontó körülmény eredete a magyar szabadalmi jogban - Papp, László (Debreceni Jogi Műhely, 2014)
It was obvious at the creation of the 37th Act of 1895 on the patent rights of inventions, that the protection of patents is a subjective right based on objective conditions, and in connection to this, the discretionality of both the monarch and any other state organizations. For the purposes of this act, the requirements of petantibility were: novelity; invetnion; susceptible of industrial application. Some of these criteria the article is presented the novelity, especially the case of publicly used. Under the first patent act, any new invetion capebla of being used industrialy can be patented, except medicines, food for men and animals, and chemical products, and if the Goverment opposes, warlike inventions. An invention was new, if it had not been published in print anywhere, or publicly worked, or patented by others in the realm. As a result the study is presented the evolituon of „publicly used” from the first patent act by the end of the second world war.